Does Tobacco Consumption Influence Outcome of Oral Mucosa Graft Urethroplasty? - Sinha, Rahul Janak; Singh, Vishwajeet; Sankhwar, S N (Urology Journal, 2010)
Introduction: In a prospective study, outcome of oral mucosa graft urethroplasty (OMGU) was assessed in patients suffering from stricture of the urethra. Materials and Methods: Patients who underwent OMGU between July 2005 and December 2007 were included in this prospective study. Forty-eight patients with stricture of the urethra were divided into 2 groups of those who consumed tobacco and had poor oral hygiene and those who did not consume tobacco and had satisfactory oral hygiene. The oral cavity was inspected. The type of tobacco consumption and the duration of exposure to tobacco were noted. The mean follow-up was 18.2 months (range, 6 to 36 months). The patients were evaluated to assess the outcome of OMGU. Results: The final outcome was analyzed in 42 patients. Thirty-one patients were asymptomatic and/or satisfied with their urinary flow rate, who were considered to have a successful outcome (73.8 %). Successful outcome in patients who consumed tobacco was significantly less (58.3%) compared to that in the tobacco nonusers (94.4%; P = .008). Conclusion: Failure rate of OMGU was higher in patients who consumed tobacco and had a poor oral hygiene, which might be due to adverse effects of these substances on the oral mucosa, leading to a poor graft quality.